Matrilin-3 Role in Cartilage Development and Osteoarthritis - Muttigi, Manjunatha S. (Int J Mol Sci, 2016)
The extracellular matrix (ECM) of cartilage performs essential functions in differentiation and chondroprogenitor cell maintenance during development and regeneration. Here, we discuss the vital role of matrilin-3, an ECM protein involved in cartilage development and potential osteoarthritis pathomechanisms. As an adaptor protein, matrilin-3 binds to collagen IX to form a filamentous network around cells. Matrilin-3 is an essential component during cartilage development and ossification. In addition, it interacts directly or indirectly with transforming growth factor β (TGF-β), and bone morphogenetic protein 2 (BMP2) eventually regulates chondrocyte proliferation and hypertrophic differentiation. Interestingly, matrilin-3 increases interleukin receptor antagonists (IL-Ra) in chondrocytes, suggesting its role in the suppression of IL-1β-mediated inflammatory action. Matrilin-3 downregulates the expression of matrix-degrading enzymes, such as a disintegrin metalloproteinase with thrombospondin motifs 4 (ADAMTS4) and ADAMTS5, matrix metalloproteinase 13 (MMP13), and collagen X, a hypertrophy marker during development and inflammatory conditions. Matrilin-3 essentially enhances collagen II and aggrecan expression, which are required to maintain the tensile strength and elasticity of cartilage, respectively. Interestingly, despite these attributes, matrilin-3 induces osteoarthritis-associated markers in chondrocytes in a concentration-dependent manner. Existing data provide insights into the critical role of matrilin-3 in inflammation, matrix degradation, and matrix formation in cartilage development and osteoarthritis.